Towards principled oceans governance : Australian and Canadian approaches and challenges - Rothwell, Donald, 1959-; VanderZwaag, David L. (Routledge advances in maritime research ;, 2006)
Australia and Canada have been at the forefront of efforts to operationalize integrated oceans and coastal management. Throughout the 1990s both countries devoted considerable effort to developing strategies to give effect to international ocean management obligations.This key book focuses on principles of marine environmental conservation and management, maritime regulation and enforcement, and regional maritime planning and implementation. With contributions from respected scholars, this informative book collectively assesses the obligations, compliance, implementation and trends i.